Estimation of Aboveground Carbon Stock in Oil Palm Plantations on Tapung Peatland, Kampar, Riau - Fatonah, Siti; Yulianti, Githa Adennita; Yusfiati, Yusfiati; Yulminarti, Yulminarti; Fitmawati, Fitmawati (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Climate change driven by greenhouse gas emissions highlights the need to estimate carbon stocks in various ecosystems, including peatlands increasingly converted into oil palm plantations. This study aimed to estimate aboveground carbon (AGC) stocks in oil palm plantations on Tapung peatland, Kampar, Riau. The research was conducted from February to August 2025 in Pagaruyung, Air Terbit, and Sungai Putih villages using purposive sampling with 0.05 ha circular plots. Tree biomass and necromass were estimated with allometric equations, while understory and litter were measured directly. Results showed total carbon stocks ranged from 21.43 to 24.78 ton/ha, with the highest in Air Terbit (24.78 ton/ha), followed by Pagaruyung (23.30 ton/ha), and Sungai Putih (21.43 ton/ha). Oil palm trees were the main contributors (±15–17 ton/ha), followed by necromass (6–9 ton/ha), whereas litter (0.14–0.20 ton/ha) and understory (0.03–0.05 ton/ha) contributed minimally. Variations were influenced by tree age, canal conditions, and plantation management. The study concludes that oil palm trees dominate AGC storage, while necromass provides medium-term carbon reserves. Management recommendations include maintaining oil palm stands, utilizing frond necromass, and sustainably managing litter and understory to support climate change mitigation.